Bu-Fei-Huo-Xue capsule alleviates bleomycin-induced pulmonary fibrosis in mice through modulating gut microbiota - Haibo Hu; Fengchan Wang; Ping Han; Peng Li; Kun Wang; Huan Song; Guojing Zhao; Yue Li; Xuechao Lu; Weihong Tao; Huantian Cui (Frontiers Media S.A., 2023)
Introduction: Bu-Fei-Huo-Xue capsule (BFHX) has been used to treat pulmonary fibrosis (PF) in clinic. However, the mechanism of Bu-Fei-Huo-Xue capsule on pulmonary fibrosis remains unclear. Recent studies have shown that the changes in gut microbiota were closely related to the progression of pulmonary fibrosis. Modulating gut microbiota provides new thoughts in the treatment of pulmonary fibrosis.Methods: In this study,a mouse model of pulmonary fibrosis was induced using bleomycin (BLM) and treated with Bu-Fei-Huo-Xue capsule. We firstly evaluated the therapeutic effects of Bu-Fei-Huo-Xue capsule on pulmonary fibrosis model mice. Besides,the anti-inflammatory and anti- oxidative effects of Bu-Fei-Huo-Xue capsule were evaluated. Furthermore, 16S rRNA sequencing was used to observe the changes in gut microbiota in pulmonary fibrosis model mice after Bu-Fei-Huo-Xue capsule treatment.Results: Our results showed that Bu-Fei-Huo-Xue capsule significantly reduced the collagen deposition in pulmonary fibrosis model mice. Bu-Fei-Huo-Xue capsule treatment also reduced the levels and mRNA expression of pro-inflammatory cytokines and inhibited the oxidative stress in lung. 16S rRNA sequencing showed that Bu-Fei-Huo-Xue capsule affected the diversity of gut microbiota and the relative abundances of gut microbiota such as Lactobacillus, Lachnospiraceae_NK4A136_group, and Romboutsia.Conclusion: Our study demonstrated the therapeutic effects of Bu-Fei-Huo-Xue capsule on pulmonary fibrosis. The mechanisms of Bu-Fei-Huo-Xue capsule on pulmonary fibrosis may be associated with regulating gut microbiota.